(3ef efXhQ ESdGejs - (3MSjf eMeO(B, (3SeMGfs; (3GHQGgje NQjS(B, (3eMehO MSjf GdhGOjs ((3YeGf(B:s (3OGQ UaGA(B,s, 2010)
(3GdeGdjI GdYGeI aj GdfXGe GdGbJUGOj GdGSdGej , GdEjQGOGJ GdYGeI aj GdOhdI GdESdGejI , GdVQGFH h GdRcGI aj GdOhdI GdGSdGejI , fabGJ GdOhdI GdGSdGejI , GdehGRfI GdYGeI h GdQbGHI GdeGdjI aj GdOhdI GdGSdGejI , GdSjGSI GdeGdjI h GdfbOjI aj GdfXGe GdeGdj GdGSdGej (B.s
(3eQGLY U(B.247s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdSjGSI GdeGdjI(B- (3GdESdGes; (3GdeGdjI GdYGeIs